Gambaran Penyakit Komorbid pada Lansia yang dirawat dengan Covid-19 di Rs Bhayangkara Pekanbaru - Elia Reski Naya; Didi Kurniawan; Musfadi Rustam (Jurnal Vokasi Keperawatan (JVK), 2022)
Introduction: Elderlyris someone who has entered the age of 60 years and over who is very susceptible to infection with therCOVID-19 virus, especially if the elderly are accompanied by comorbidities. The purposeri of this study was to determine the description of comorbid diseases in the elderly who were treated with COVID-19. Methods: This studyrused an analytical survey research design with a retrospective study approach. The sample used in this study was 58 people who were taken side by side from January 2021 to March 2022. Collecting data obtained indirectly, namely secondary data from the Medical Records of Bhayangkara Hospital Pekanbaru. Results: From the 58 respondents studied, it can be concluded that the majority of respondents are male, the majority of respondents are in the age range of 60-74 years totaling 49 people. The Results showed that the most comorbid diseases in the elderly were diabetes mellitus (62.1%), hypertension (37.9%), dyspepsia (36.2%), dyslipidemia (22.4%), liver infection (17.2%). ), and accompanied by other diseases. Conclusion: The results of this studyrindicate thatrthe majority of respondents who are susceptible to infection with therCOVID-19r virus are men and thermostat comorbid disease suffered by the elderly is diabetes mellitus.